PROSEDUR PENGELOLAAN SURAT MASUK DAN SURAT KELUAR PADA BAGIAN UMUM DAN KEPEGAWAIAN KANTOR DINAS PENDIDIKAN PROVINSI SULAWESI SELATAN - Husni Bt Salam; Adi Siswanto (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2022)
This study aims to describe the procedure for managing incoming and outgoing mail in the General and Personnel section. The type of research used is descriptive qualitative, namely the author describes the results of observations, interviews, documentation and analyzes the data obtained in the field. The author of this final project is the result of research conducted from May to June 2020. The results showed that the process of managing incoming and outgoing letters in the general and staffing section, namely incoming mail, starts from receiving letters, scheduling letters, directing letters, storing letters. While the outgoing letter starts from drafting the letter, approval of the letter concept, typing the concept, giving the coordination stamp, signing the letter, recording the letter, storing the letter. The procedure for managing letters at the education office is running optimally.